Design and Implementation of Intelligent Entrance Guard Lock Based on NB-IoT - ZHANG Tianqi;WANG Jin;LI Yuehua (Nantong Daxue xuebao. Ziran kexue ban)
The key of conventional mechanical lock is easy to be lost and duplicated; the password entrance guard lock shares similar problems, like the high possibility of leaking and forgetting the password; the entrance guard lock based on Wi-Fi is limited by the scope of the network. In order to solve these problems, a smart access control lock based on the narrow-band internet of things(NB-IoT) is proposed, which uses fingerprint as the identity information,and NB-IoT technology as a communication method. The system is mainly composed of peripherals, controllers,NB-IoT modules, information post offices and other modules, which can realize the functions of fingerprint collecting,fingerprint matching, fingerprint deleting, image collecting and transmitting, visit reminding, remote door opening and alarming. The tests confirm all the effectiveness of all the functions. Finally, the access control system is compared with access control locks based on RFID technology, Wi-Fi technology, and Bluetooth technology, the findings show that the smart lock identification based on NB-IoT technology and fingerprint recognition technology is the fastest and the most accurate one, difficult to be duplicated. It enjoys the advantages of wider network coverage, less power consumption, and more secure identity information.